Synthesis, Properties, and Environmental Impact of Hybrid Pigments - Kawaljit Singh Randhawa (The Scientific World Journal)
This article investigates the evolving domain of hybrid pigments, which integrate both organic and inorganic constituents to yield novel color properties and enhanced performance. Beginning with an overview of their significance across industries, the study delves into various types of hybrid pigments, focusing on synthesis techniques and recent advancements. The study examines their utilization in paints, inks, plastics, and cosmetics, emphasizing their ability to meet industrial demands. Critical factors such as color stability, lightfastness, and environmental impact are evaluated, with a focus on sustainability metrics. The review encompasses diverse aspects including synthesis methods, color stability, applications across sectors, and environmental considerations of hybrid pigments.